The dual role of Parylene C in chemical sensing: Acting as an encapsulant and as a sensing membrane for pH monitoring applications - Trantidou,T; Payne,DJ; Tsiligkiridis,V; Chang,Y-C; Toumazou,C; Prodromakis,T (Sensors and Actuators B - Chemical, 2013)
In this work, we demonstrate a new property of Parylene C emphasizing on its application in pH sensing technologies. For many decades the material has been extensively used as a biocompatible inert encapsulant of implantable micro-devices. Toward a new understanding of the material's potential, we explore the transformation of Parylene C from a passive encapsulation membrane into an active H+ sensing membrane using discrete MOSFETs to evaluate its chemical sensing performance. We employ oxygen plasma treatment to functionalize Parylene's H+ sensing capacity and enhance the chemical sensitivity, drift rates, and reliability of the sensing devices. Moreover, we demonstrate a versatile technique that enables the deployment of the material both as an encapsulant and as a sensing membrane in a single platform, in order to benefit from distinguishable and consistent sensitivities, and low leakage currents during pH measurements. Our investigation reveals that the selective modification of Parylene's surface chemistry yields reliable pH sensing devices, ensuring the best combination of sensitivity (16.3 mV/pH) and leakage currents (6–10 nA) over a reasonably wide pH range (4–10), while drift rates remain in low levels (2.5–20 mV/h). We believe that this study opens up new application horizons for Parylene, which is a new promising material in the emerging field of flexible electronics able to deliver low film thicknesses and high biocompatibility, while facilitating the application of mechanical stimulus.